To Pass (or Not to Pass) Through International Fuel Price Changes to Domestic Fuel Prices in Developing Countries : What Are the Drivers? - Kpodar, Kangni; Imam, Patrick (Washington, D.C. : International Monetary Fund, 2020)
While many developing countries limit the international fuel price pass through to domestic fuel prices, others do not. Against this backdrop, we examine the factors that determine whether governments allow international fuel price changes to be passed through to domestic prices in developing countries using a dataset spanning 109 developing countries from 2000 to 2014. The paper finds that the pass-through is higher when changes in international prices are moderate and less volatile. In addition, the flexibility of the pricing mechanism allows for higher pass-through while exchange rate depreciation and lower retail fuel prices in neighboring countries inhibit it. The econometric results also underscore the fact that countries with inflation tend to experience lower pass-through, whereas those with high public debt exhibit larger pass-through. Finally, no evidence is found that political variables or environmental policies matter with regard to fuel price dynamics in the short-term. These findings, which are consistent across fuel products (gasoline, diesel and kerosene), allow us to draw important policy lessons for fuel subsidy reforms.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet